Cu2+/ATP reversible ratiometric fluorescent probe through strip, hydrogel, and nanofiber, and its application in living cells and edaphic ecological safety assessment. (November 2020) - Jin, Xilang; Wu, Xianglong; Zhang, Fei; Zhao, Huaqi; Zhong, Wei; Cao, Yixin; Ma, Xuehao; Leng, Xin; Zhou, Hongwei; She, Mengyao
Abstract: Specific and visual detection of copper ion (Cu 2+ ) and ATP was critical for environmental and biological fields. In this work, a new rhodol-based ratiometric fluorescent probe for the reversible recognition of Cu 2+ and ATP was designed under theoretical analysis. The Cu 2+ /ATP-induced emission intensity showed linearly proportional to the Cu 2+ /ATP concentration (0.0–10.0 μM) with the low detection limit of 0.11 μM/0.08 μM. Due to its excellent spectral properties, the reversible detection of Cu 2+ and ATP was exploited through test strips and hydrogel. More importantly, Electrospun PMMA doped with the probe was constructed as a fluorescent sensing platform for specific and visual detection of Cu 2+ under UV lamp by the naked eyes and the fluorescent sensing platform could be efficiently regenerated and recycled for several times by the treatment with ATP solution. Furthermore, the probe was applied to visualize Cu 2+ and ATP in living cells and determine the content of Cu 2+ in real soil samples which demonstrated the first reported probe for Cu 2+ with application in edaphic ecological safety assessment. We prospected that this present work could promote the potential applications of fluorescent sensing platform in multifunctional environmental and biological portable sensing devices. Graphical abstract: Image 1 Highlights: A ratiometric fluorescent probe for the reversible recognition of Cu 2+  and ATP was designed under theoretical analysis. The probe composited PMMA fluorescent sensing platform was constructed to detect the trace amounts of Cu 2+  by naked eyes. This work promoted the potential applications of fluorescent platform in environmental and biological portable sensing devices.